Analysis of cоmpetitive shooting of the world top female biathletes and female biathletes of the national team of Ukraine - Roman Zubrilov; Olena Pidhrushna (Kharkiv State Academy of Physical Culture, 2016)
Purpose: optimization of preparation of highly skilled female biathletes on the basis of determining the required number of shots that provides optimum prerequisites for stable performance at the season major competition. Material & Methods: analysis of scientific-methodical literature; theoretical methods of scientific cognition; methods of mathematical statistics. Results: average percentage of hits of the World and Olympic champions and prizewinners (2006-2015) has been calculated. It constitutes 84,47% during 420 shots performed per season. It has been revealed that in 86,42% of cases the high quality of shooting is provided by 340÷500 shots performed per season. Conclusions: in order to medal at the season major competition one should have the level of shooting preparation equal to 84÷85% hits per season, minimum possible quality of shooting along with excellent racing preparation - 79,5%. 160-280 competitive shots performed per season could provide stable performance at the major competition.